Research on the Influence of Evolution of Landscape Patterns of Blue-Green Space on the Cooling Effect in the Central Urban Area of Xi’an - Weiying KONG; Yizhuo LIU; Sichun DONG; Yuandong HU (Fengjing Yuanlin)
ObjectiveIn the contemporary global context, urban areas are increasingly confronted with the dual pressures of global climate change and rapid urbanization. These pressures have led to a significant rise in urban temperature, thereby amplifying the importance of blue-green spaces in mitigating the urban heat island (UHI) effect. Blue-green spaces, which include natural water bodies, parks, green corridors, and other vegetated areas, play a crucial role in regulating urban microclimates. As cities enter an era of stock development, where the focus shifts from expansion to optimization of existing resources, the strategic configuration of these spaces has become a cornerstone for enhancing urban thermal environments. Understanding the cooling mechanisms of blue-green spaces at various spatial scales is essential for improving urban thermal comfort and guiding the planning and construction of urban blue-green infrastructure.MethodsThis research focuses on the central urban area of Xi’an, a city that has experienced substantial urban growth over the past decade. By employing a combination of spatial autocorrelation analysis and a multi-scale geographically weighted regression (MGWR) model, the research examines the change characteristics of blue-green spaces and their impact on land surface temperature from 2013 to 2023. The findings reveal the spatial heterogeneity of cooling effects and offer tailored optimization strategies for blue-green spaces across diverse urban contexts. The research methodology involves selecting six representative landscape indices to evaluate the changes in blue-green space patterns in the central urban area of Xi’an. These indices are carefully chosen to capture the nuances of spatial configuration, fragmentation, and connectivity of blue-green spaces. Spatial autocorrelation analysis is utilized to identify spatial clustering and patterns extracted from the data collected, while the MGWR model is adopted for a more granular examination of the relationship between landscape indices and land surface temperature levels. This integrated approach not only reveals the factors influencing the cooling effects of blue-green spaces but also highlights their spatial variability across the urban landscape.ResultsThe results of the research are both revealing and instructive. 1) The blue-green space patterns in the central urban area of Xi’an underwent significant changes over the research period, reflecting the dynamic interplay between urban development and environmental management. 2) The spatial distribution of land surface temperature exhibits a distinct pattern of being “high in the north and low in the south”. The central area, characterized by dense urban fabric, shows minimal fluctuations in land surface temperature, whereas low-temperature zones are predominantly concentrated in the southern part of Baqiao District. This uneven thermal distribution underscores the complexity of urban heat dynamics and the need for targeted interventions. 3) The relationship between landscape indices and land surface temperature changes displays notable spatial heterogeneity. In high-density urban areas, small and complex blue-green patches demonstrate stronger cooling effects, emphasizing the importance of intricate designs in densely built environments where space is limited but the need for effective cooling is significant. In contrast, suburban areas benefit from avoiding the aggregation of large blue-green patches, which may otherwise hinder effective cooling due to reduced air circulation and increased shading. Near large water bodies, regularly shaped and highly connected blue-green patches are found to be particularly effective in reducing land surface temperature, highlighting the synergistic effects of water and vegetation in enhancing cooling performance and suggesting that integrated blue-green networks can maximize thermal benefits.ConclusionThe research concludes that the relationship between temperature changes and blue-green space changes in the central urban area of Xi’an is significant and characterized by strong spatial heterogeneity during the period from 2013 to 2023, with the cooling effects of blue-green spaces found varying by their spatial attributes and the characteristics of the surrounding urban environment. These findings highlight the necessity for region-specific optimization strategies to maximize the cooling potential of blue-green spaces. By integrating spatial analysis and regression modeling, the research provides a detailed understanding of the cooling mechanisms of blue-green spaces across diverse urban contexts. The results emphasize the importance of tailoring blue-green space designs to local conditions, considering factors such as urban density, proximity to water bodies, and regional climatic characteristics. This approach enhances the effectiveness of blue-green spaces in mitigating the urban heat island effect and contributes to the creation of more sustainable and thermally comfortable urban environments. The research advocates a holistic and adaptive urban planning strategy, where blue-green spaces are strategically designed and managed to address the unique thermal challenges of different urban areas. This research offers valuable guidance for policymakers and urban planners aiming to optimize blue-green infrastructure and improve urban resilience in the face of climate change and urbanization.